Assessment of eLearning Tools Utilized by IT Faculty of Programming Course in the New Normal (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Students’ knowledge relies on the hand of their teacher. The use of different learning modalities like utilization of hand-outs, visual aids using paper or presentation, and the internet helps to impart knowledge to the learners. Learning process is not limited in school alone, rather it continues even at home. With the current setting where face-to-face classes are prohibited due to pandemic, teachers need to be more innovative which helps not to disrupt the continuous learning of the students.  This study will present discussions on the assessment of eLearning teaching tools utilized by IT faculty of programming course. The researcher conducted a descriptive research and used survey questionnaire for data collection. Teachers used different eLearning tools in instruction delivery. The technological factors greatly help on the success of eLearning tool implementation in the new normal. The learning management system tools used in distance learning has valuable effect on students when interacting with the instructor. Faculty members of programming course used Microsoft Teams as the Learning Management System with Google Classroom, Schoology, Facebook Page, or Messenger as the secondary medium for interaction. The assessment results showed that majority of the students are highly satisfied with the features, functions, and support provided by the tools. Further studies must be conducted to address the performance of the students and teachers during the implementation of these eLearning tools in the new normal.